The psychological therapy preferences of patients who hear voices. Issue 1 (2nd January 2023) - Berry, Clio; Baloc, Andreea-Ingrid; Fowler, David; Jones, Anna-Marie; Hazell, Cassie M; Hayward, Mark
ABSTRACT: Background: Voice-hearing is a common, phenomenologically diverse, experience across different mental health diagnoses. Patient preferences for psychological therapies are helpful in informing treatment commissioning and provision, especially in the context of complex and variable experiences like voice-hearing. There is, however, very limited evidence as to the psychological therapy preferences of transdiagnostic voice-hearers. Methods: Three-hundred and thirty-five voice hearers were recruited from secondary care NHS mental health services across England, between 2020 and 2022. Participants completed a questionnaire battery, involving a psychological therapy preference survey. Participants ranked their preferences across categories of practical, technical and relational therapy elements. Therapy preferences were examined using non-parametric ANOVAs and the significance of pairwise comparisons between different therapy elements. Results: There were significant differences in all categories of preference elements. Clear hierarchies of preference were observed in therapy location, timing, delivery, and therapy approach. Preferences were evident, albeit with less clear vertical hierarchies, for number of sessions, mode, therapist qualities, and therapy focus, tasks and outcomes. Discussion: Overall, participants expressed a preference for individual, face-to-face intervention of at least nine sessions, with a highly experienced therapist and a core focus on enhancing coping strategies for voice-hearing experiences.